Synergistic activity of Coptis Chinensis and clotrimazole against Candida Albicans - Wan-Yun Feng; Un-Ieng Cheang; Ka-I Wong; Hio-Ian Cheong; Li-Rong Meng; Pedro Fong (Elsevier, 2023)
Introduction: Candida albicans is an important and widespread opportunistic pathogen. In recent years, studies have found that traditional Chinese medicine (TCM) can inhibit the growth of various types of fungi without inducing drug resistance. This study aims to investigate the anti-C. albicans abilities of four types of TCM extracts, namely Oroxylum indicum, Coptis chinensis, Verbena officinalis and Ramulus cinnamomi. Materials and methods: Oxford cup assays were employed to determine the sensitivity of C. albicans to the TCM extracts and establish the initial effective concentrations for further experiments. Broth microdilution methods and checkerboard microdilution assays were used to determine the C. albicans inhibition activities of the individual TCM extract and their combinations with clotrimazole and eugenol. Results: Among the four TCM extracts, C. chinensis had the highest potency against C. albicans, indicated by the minimum inhibitory concentration (MIC50) and minimum fungicidal concentration (MFC) values of 30 and 60 mg/mL, respectively. The C. chinensis extract also potentiated the anti-C. albicans activity of clotrimazole, indicated by a fractional Inhibitory concentration index (FICI) of 0.25. Both O. indicum and V. officinalis showed additive effects on C. chinensis in the TCM combinations. The combination of clotrimazole (a Western medicine compound) and eugenol (a TCM ingredient) had a weak additive effect with a FICI value of 1.0. Conclusion: This study supports further investigations of C. chinensis for the development of adjuvant therapeutic agents to current anti-fungal treatment against C. albicans infection.